2017
DOI: 10.1542/peds.2017-0432
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ Bullying: Translating Research to Action in Pediatrics

Abstract: Lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth experience significant bullying that undermines their mental and physical health. National health organizations have called for the development of innovative strategies to address LGBTQ bullying. Pediatricians and other clinicians, medical and public health students, interdisciplinary researchers, government officials, school leaders, community members, parents, and youth from around the country came together at a national symposium entitled "LGBTQ B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 50 publications
0
31
1
1
Order By: Relevance
“…Schools can establish GSAs if not already present; these groups often conduct awareness and education events as well as advocate within the school for LGBTQ issues. Further, programs that focus specifically on bias-based bullying may be needed, in addition to general bullying prevention programs, to address stigma present within schools and communities (Earnshaw et al 2017(Earnshaw et al , 2018. Of note, we did not find that LGBTQ-supportive schools or communities protected LGBQ youth from general bullying victimization.…”
Section: Implications For Practicecontrasting
confidence: 54%
See 1 more Smart Citation
“…Schools can establish GSAs if not already present; these groups often conduct awareness and education events as well as advocate within the school for LGBTQ issues. Further, programs that focus specifically on bias-based bullying may be needed, in addition to general bullying prevention programs, to address stigma present within schools and communities (Earnshaw et al 2017(Earnshaw et al , 2018. Of note, we did not find that LGBTQ-supportive schools or communities protected LGBQ youth from general bullying victimization.…”
Section: Implications For Practicecontrasting
confidence: 54%
“…Of note, we did not find that LGBTQ-supportive schools or communities protected LGBQ youth from general bullying victimization. Research has not yet examined whether general bullying prevention programs that do not address bias reduce bullying victimization among LGBQ youth (Earnshaw et al 2017), but it is likely that changing interpersonal and structural stigma will be difficult (Hatzenbuehler and Pachankis 2016). Programs to cultivate LGBTQ-supportive communities and provide supportive LGBTQ school resources may create climates that reduce bias-based bullying and better support LGBQ youth, particularly girls.…”
Section: Implications For Practicementioning
confidence: 99%
“…Currently, the debate is still continuing with the development of the ICD-11 (18). Research is ongoing on the way to facilitate access to care for transgender people, to better meet their needs, but also on educational and informational programs to reduce transphobia and discriminations that are considered to contribute to dysphoria and comorbid conditions in transgender youth (19,20).…”
Section: History Of Transgender Care In Children and Adolescentsmentioning
confidence: 99%
“…Finally, the mental health professional offers supportive psychotherapy that focuses on exploring gender identity, alleviating distress and helping youth to develop a positive personal selfconcept. To promote an accepting and nurturing response, support by family but also by school, health professionals and in general all the people who surround the child or adolescent is essential(19,65). Indeed, different studies have shown the negative impact of social stigmatization, while family and school support are protective factors(19,66,67,68,69).…”
mentioning
confidence: 99%
See 1 more Smart Citation